Sosialisasi Strategi Pemasaran Usaha Budidaya Ikan Lele Di Pokdakan Mina Buana Kabupaten Kediri - Erlin Widya Fatmawati (Jurnal Pengabdian Masyarakat IPTEK, 2023)
The purpose of this community service is to implement a marketing strategy for the catfish farming business at Pokdakan Mina Buana and provide assistance for the manufacture of processed catfish that has more selling value. Problems faced by partners include the inactivity of several members of the pokdakan, marketing of catfish which is still limited to 1 middleman, catfish harvests must be sold immediately due to limitations in fish weight, and the product of cultivation is still fresh catfish, there is no processing. more varied catfish. The solutions given to the problems above include; there is guidance and a more intensive approach to several members of the pokdakan, it is necessary to develop a marketing strategy to areas outside Kediri Regency, the pokdakan makes a schedule for seeding, administering vaccines, until the harvest schedule, it is recommended to make processed catfish products in the form of frozen and added yellow seasoning , presents the trademark on catfish and processed products..